Assessment by ABPM verified the presence of hypertension in patients with self-reported hypertension, pregnant women, as well as differences between ethnicities in women aged 38-39 years in the Ribeirão Preto cohort - Brandão, Tetzi Oliveira (2022)
Introduction: Arterial hypertension is a global health problem and one of the main risk factors for cardiovascular diseases (CVD), and therefore for morbidity and mortality among adult men and women. Factors related to obstetric history, family history, sociodemographic characteristics, and lifestyle habits are known determinants of arterial hypertension. Methods: Case-control study of women belonging to the 1978/79 birth cohort conducted in the city of Ribeirão Preto/SP. Sociodemographic data, presence of comorbidities, maternal comorbidities, paternal comorbidities, comorbidities during pregnancy, and biometric and biophysical markers associated with blood pressure measured by 24-h ambulatory blood pressure monitoring (ABPM) were assessed in women aged 38–39 years. We want to study which variables of the previous sentence are related to the presence of hypertension measured by ABPM. Results: Data from 281 women were analyzed. Our results showed that ethnicity, a history of hypertension, and gestational hypertension reported by the women were significantly associated with the presence of hypertension measured by ABPM. Other factors such as marital status, educational level, comorbidities of the woman, paternal or maternal comorbidities, anthropometric measurements or serum levels of cardiovascular markers were not associated with the presence of hypertension measured by ABPM. Conclusion: We conclude that ethnicity, self-reported hypertension, and gestational hypertension are associated with arterial hypertension measured by ABPM.